Biochemical Correlates of Video Game Use: From Physiology to Pathology. A Narrative Review - Barbara Carpita; Dario Muti; Benedetta Nardi; Francesca Benedetti; Andrea Cappelli; Ivan Mirko Cremone; Claudia Carmassi; Liliana Dell’Osso (Life, 2021)
In the last few decades, video game playing progressively became a widespread activity for many people, in childhood as well in adulthood. An increasing amount of literature has focused on pathological and non-pathological correlates of video game playing, with specific attention towards Internet Gaming Disorder (IGD). While many neurobiological studies in this field were based on neuroimaging, highlighting structural and functional brain changes among video game users, only a limited number of studies investigated the presence of biochemical correlates of video gaming. The present work aims to summarize and review the available literature about biochemical changes linked to video game use in IGD patients as well as non-pathological users, and the differences in between. Results may shed light on risks and benefits of video games, providing directions for further research on IGD treatment and, on other hand, on the potential role of video games in therapeutic or preventive protocols for specific conditions.